Processability of polypropylene/multiwalled carbon nanotube nanocomposites via direct melt compounding - ABD RAZAK , JEEFFERIE; Mohamad, Noraiham; Ab Maulod, Hairul Effendy (SAGE Publications, 2013)
This article presents the effect of filler loading on compounding torques as well as mechanical properties of polypropylene/multiwalled carbon nanotube (PP/MWCNTs) nanocomposites. Samples were prepared via melt compounding method using a Haake internal mixer at rotor speed of 80 r/min. The torque values in a 10-min compounding period for the incorporation of MWCNTs fillers into PP matrix were analyzed and thoroughly evaluated. The data was further confirmed by morphological analysis via transmission electron microscopy. The efficiency of direct melt-compounding method using internal mixer was evident from the homogeneity of MWCNTs dispersed within the PP matrix observed in produced nanocomposites at filler loading up to 0.75 wt%. MWCNTs showed significant compatibility with PP matrix and proved the needlessness of chemical pretreatment and complicated compounding process to produce PP/ MWCNTs nanocomposites. The mechanical properties and morphological characteristics were in good correlation with the processing behavior of the nanocomposites.